2002
DOI: 10.1124/dmd.30.12.1491
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Midazolam and 1′-Hydroxymidazolam in Chinese with Different CYP3A5 Genotypes

Abstract: ABSTRACT:The CYP3A subfamily represents the most abundant cytochrome P450 in the human liver and gastrointestinal tract and plays very important role in xenobiotic metabolism. CYP3A5 is expressed in a relatively small population of whites and Orientals. We recruited 42 Chinese volunteers to determine the genotypes of CYP3A5 by polymerase chain reaction-restriction fragment length polymorphism. Genotype analyses revealed that CYP3A5*3 allele existed in 39 of 42 volunteers. CYP3A5*4 and CYP3A5*5 alleles were fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
81
3

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(101 citation statements)
references
References 22 publications
16
81
3
Order By: Relevance
“…Interestingly, a similar result has been obtained in the case of midazolam, a typical CYP3A5 substrate. Namely, midazolam pharmacokinetics was also hardly influenced in vivo by the genotype of CYP3A5, 18 although midazolam is metabolized in vitro by CYP3A5 rather than CYP3A4. 3,17,19 Several possibilities can be proposed to explain these discrepancies between the in vitro and in vivo data.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a similar result has been obtained in the case of midazolam, a typical CYP3A5 substrate. Namely, midazolam pharmacokinetics was also hardly influenced in vivo by the genotype of CYP3A5, 18 although midazolam is metabolized in vitro by CYP3A5 rather than CYP3A4. 3,17,19 Several possibilities can be proposed to explain these discrepancies between the in vitro and in vivo data.…”
Section: Discussionmentioning
confidence: 99%
“…Results of PAGE are illustrated in Fig. 2. CYP3A4 isoenzymes are responsible for the metabolism of > 50% of drugs such as steroid components, antidepressant, antibiotics, ... [4]. Pharmacogenetic studies show that genetic variations in this gene and other genes of CYP450 superfamily (specially polymorphism) can affect metabolism process of drugs [1].…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, CYP3A4 enzyme product is responsible for over 50% of all clinically drug products [3]. These drugs are included steroids immunosuppressive agent [4]. Also, CYP3A4 is responsible for the conversion of testosterone to less biologically active forms of this hormone, such as 2β, 6β, and 15β-hydroxy testosterone [5].…”
Section: Introductionmentioning
confidence: 99%
“…Kuehl et al [11] showed that G/A (44 polymorphism in CYP3AP1 was linked to the splicing defect of CYP3A5*3/*1. Shih et al [12] also showed that G/A (44 polymorphism of CYP3AP1 promoter has strong association with a/g 22893 polymorphism in intron 3 of CYP3A5 in Chinese. Both of them showed that the patients carrying CYP3AP1*1 also carried CYP3A5*1, in the same way, patients carrying CYP3AP1*3 also carried CYP3A5*3 and patients carrying CYP3AP1*1/*3 also carried CYP3A5*1/*3.…”
mentioning
confidence: 99%